Synthesis of 2-[(3,4,5-Triphenyl)phenyl]acetic Acid and Derivatives - Monika Mazik; Pierre Seidel (Molbank, 2024)
New phenylacetic acid derivatives with potentially valuable biological activities and the ability to act as starting materials for various functionalizations have been prepared by a multi-step synthesis. Starting from 2,6-dibromo-4-methylaniline, the synthetic route involves the construction of the basic aromatic structure (3,4,5-triphenyltoluene) (two steps), followed by its conversion into 2-[(3,4,5-triphenyl)phenyl]acetic acid and derivatives (up to five steps). Based on this multi-step synthesis, five compounds not previously reported in the literature were synthesized; the literature-known 3,4,5-triphenyltoluene was synthesized for the first time in the manner described. This synthesis is applicable for the preparation of numerous new representatives of this class of compounds.